Corporate strategy and product innovation - Rothberg, Robert R. (New York : Free Press, 1981)
This second edition contains a number of changes . They reflect new realities in the socio-economic and technological environment as well as the availability of significant new material. While a good deal of the content differs from the first edition, the basic organizing principles remain the same. One change in the second edition is the new emphasis given to the role of law government as a stimulus and barrier to innovation.
Includes index.
Includes bibliographical references p. 510-515 and index.
hza 26/07/2018
Loans
Keywords: New products; Product management